Perovskite composition and preparation method and application thereof

By using specific additives in perovskite solar cells to adjust the performance of the perovskite film, the stability and efficiency issues of perovskite solar cells are solved, and more efficient and stable photoelectric conversion effects are achieved.

CN119365051APending Publication Date: 2025-01-24GUANGDONG MINGYANG FILM TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411311753.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Perovskite solar cells face stability and efficiency problems in commercial applications, especially because organic matter is susceptible to environmental factors, resulting in reduced performance and shortened lifetime.

Method used

A composition of a perovskite, including (FA0.95MA0.05) 0.95CS0.05PB (i0.95br0.05) 3 and specific additives, such as 1-Cindy-3-metimimazole tetrafluorosilicate salt salt , 1-clone-1-methylilidine tetrafluorosyl-boric acid and 1-clone-4-methylpyamine tetrameramramel, through the N-atomic heteroid structure of these additives and BF4-anionic calcium regulatory calcium The quality of light absorption, current transmission, and interface contact quality of titanium -ore film.

Benefits of technology

Effectively improve the photoelectric conversion efficiency of perovskite solar cells, extend the service life of the battery, and enhance its stability and environmental adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005050864600000121
    Figure BDA0005050864600000121
  • Figure BDA0005050864600000131
    Figure BDA0005050864600000131
  • Figure HDA0005050864610000011
    Figure HDA0005050864610000011
Patent Text Reader

Abstract

The invention discloses a perovskite composition as well as a preparation method and application thereof. The perovskite composition is prepared from the following raw materials: (FA < 0.95 > MA < 0.05 >) < 0.95 > Cs < 0.05 > Pb < (I < 0.95 > Br < 0.05 >) < 3 > and an additive, the additive is prepared from at least one of 1-octyl-3-methylimidazolium tetrafluoroborate, 1-butyl-1-methylpiperidine tetrafluoroborate and 1-butyl-4-methylpyridine tetrafluoroborate, and the additive is prepared from at least one of 1-octyl-3-methylimidazolium tetrafluoroborate, 1-butyl-1-methylpiperidine tetrafluoroborate and 1-butyl-4- The perovskite composition provided by the invention can effectively improve the light absorption performance, the carrier transport performance and the interface contact quality of a perovskite thin film, so that the photoelectric conversion efficiency of a perovskite solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite materials, and in particular to a perovskite composition, a preparation method and an application thereof. Background Art

[0002] With the continuous growth of global energy demand and the increasingly serious environmental problems, the development and utilization of renewable energy has become a hot topic in current research. As a new type of photovoltaic device, perovskite solar cells have shown great application prospects in the photovoltaic field due to their advantages such as high photoelectric conversion efficiency, low cost and easy preparation. However, the commercial application of perovskite solar cells still faces many challenges. First, the stability problem of perovskite solar cells is particularly prominent. Since perovskite materials contain a large amount of organic matter, these substances are easily affected by environmental factors such as light and humidity, resulting in reduced battery performance and shortened life. Secondly, the efficiency problem of perovskite solar cells is also a key factor restricting their large-scale application. Although researchers have made significant progress in materials and processes in recent years, the photoelectric conversion efficiency of perovskite solar cells still needs to be further improved. In perovskite solar cells, ion migration is an important phenomenon, which may lead to unstable battery performance and reduced efficiency. Among them, ionic liquids, a class of liquid materials with unique properties, have excellent thermal stability and electrochemical stability, and have low corrosiveness to perovskite materials, and can be used to improve the stability of perovskite solar cells. Ionic liquids can effectively extend the service life of perovskite solar cells by inhibiting ion migration and reducing interface reactions. On the other hand, ionic liquids also have lower resistivity and higher ion mobility. Their introduction may improve the separation and transmission of photogenerated carriers by changing the ion distribution and migration path inside the perovskite, thereby improving the photoelectric conversion efficiency of the battery.

[0003] Therefore, it is of great significance to develop more efficient and stable ionic liquids to further improve the performance of perovskite solar cells. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a perovskite composition, which can effectively improve the light absorption performance, carrier transport performance and interface contact quality of the perovskite film, thereby improving the photoelectric conversion efficiency of the perovskite solar cell. At the same time, the ionic liquid can also inhibit the decomposition and degradation of the perovskite material and extend the life of the perovskite solar cell.

[0005] The invention also provides a perovskite film.

[0006] The invention also provides a perovskite solar cell.

[0007] According to a first aspect of the present invention, a perovskite composition is provided, wherein the raw materials for preparing the perovskite composition include:

[0008] (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and additives;

[0009] The additive comprises at least one of 1-octyl-3-methylimidazolium tetrafluoroborate, 1-butyl-1-methylpiperidinium tetrafluoroborate and 1-butyl-4-methylpyridinium tetrafluoroborate.

[0010] The present invention selects a series of additives with different cationic structures. The additives provided by the present invention are different heterocyclic structures containing N atoms and BF 4- Anionic additives have at least the following beneficial effects:

[0011] 1. The additive contains N atom heterocyclic structure and contains BF4 - The N atoms with lone pair electrons in the anionic compound of the additive ionic liquid can react with the unbound Pb atoms in the perovskite absorption layer to form covalent bonds, thereby passivating the defects of the perovskite absorption layer and reducing the non-radiative recombination of carriers, thereby improving the fill factor (FF) and short-circuit current (J) of the perovskite solar cell. sc ), and improving the efficiency and stability of perovskite solar cells; the preparation process of the ionic liquid provided by the embodiment of the present invention is simple, the raw materials are cheap and easily available, and it is suitable for industrial production and use.

[0012] 2. By selecting additives with cations and anions having specific functional groups and structures, the physical and chemical properties of ionic liquids can be regulated in the solution state to meet the performance requirements of perovskite solar cells. By selecting the ionic radius, charge distribution and interaction of cations with perovskite materials and the stability and solubility of anions. The ionic liquid with additives selected by the present invention has BF 4- Anions can adjust the band gap and energy band distribution of perovskite, thereby reducing non-radiative recombination in the carrier transport process in the perovskite absorption layer, improving the efficiency of carrier transport, and thus improving the photovoltaic performance and stability of perovskite solar cells. Further, the effects of the additive ionic liquid also include: the additive ionic liquid provided by the present invention has excellent passivation effect, good solubility and stability, and provides a reliable material basis for subsequent applications.

[0013] 3. The additive ionic liquid contains BF4 -Anions exhibit strong hydrophobicity, which can prevent water and oxygen erosion in the air, thereby improving the stability of perovskite solar cells. By regulating the addition of different ionic liquids, the morphology, crystallinity and photoelectric properties of perovskite films can be regulated.

[0014] In some embodiments of the present invention, the (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and the additive in a molar ratio of 1:0.001 to 0.005.

[0015] The above ratio is conducive to improving the crystal structure stability of the perovskite material, reducing defects in the material, inhibiting the decomposition or migration of the perovskite, thereby improving the long-term stability of the battery, avoiding the insignificant increase in open circuit voltage or the decrease in device filling, and significantly reducing efficiency.

[0016] In some embodiments of the present invention, in solution, the (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 concentration is 1~1.8mol / L.

[0017] The above concentration helps to form a uniform film and avoid crystal defects during the deposition process.

[0018] In some embodiments of the present invention, in a solution state, the solvent of the perovskite composition includes at least one of dimethylformamide and dimethyl sulfoxide.

[0019] In some embodiments of the present invention, in a solution state, the solvent of the perovskite composition includes dimethylformamide and dimethyl sulfoxide; the molar ratio of the dimethylformamide to the dimethyl sulfoxide is 4:1.

[0020] The above ratio helps to improve the solubility, viscosity, volatilization rate and crystallinity of the perovskite precursor solution, thereby helping to prepare high-quality perovskite films and ultimately improving the photoelectric conversion efficiency of solar cells.

[0021] According to a second aspect of the present invention, a perovskite film is provided. The perovskite film is prepared from the perovskite composition.

[0022] According to a third aspect of the present invention, a perovskite solar cell is proposed, comprising an anode conductive glass layer, a hole transport layer, a perovskite absorption layer, an electron transport layer, a blocking layer and a cathode layer stacked in sequence, wherein the perovskite absorption layer is the perovskite film.

[0023] In some embodiments of the present invention, the method for preparing the perovskite absorption layer comprises: coating the titanium ore composition on the hole transport layer in a solution state, adding an anti-solvent for extraction during spin coating, and then annealing to obtain the perovskite absorption layer.

[0024] In some embodiments of the present invention, the method for preparing the perovskite solar cell comprises:

[0025] S1: After UV-ozone treatment of transparent conductive glass, NiO is sputtered on the surface x , as a hole transport layer;

[0026] S2: in a solution state, coating the titanium ore composition on the hole transport layer, adding an anti-solvent for extraction during spin coating, and then performing annealing to obtain a perovskite absorption layer;

[0027] S3: depositing an electron transport layer, a blocking layer and a cathode layer in sequence on the surface of the perovskite absorption layer.

[0028] In some embodiments of the present invention, the material of the transparent conductive glass includes: FTO glass or ITO glass.

[0029] In some embodiments of the present invention, in step S2, the coating includes spin coating, the spin coating speed is 4000-4500 rpm, the annealing temperature is 100-120° C., and the annealing time is 30-50 min.

[0030] In some embodiments of the present invention, the thickness of the cathode layer is 100-120 nm.

[0031] In some embodiments of the present invention, the material of the electron transport layer includes C60.

[0032] In some embodiments of the present invention, the material of the barrier layer includes SnO2.

[0033] The perovskite absorption layer prepared by the additive ionic liquid can effectively improve the light absorption performance, carrier transport performance and interface contact quality of the perovskite film, thereby improving the photoelectric conversion efficiency of the perovskite solar cell. At the same time, the ionic liquid can also inhibit the decomposition and degradation of the perovskite material and extend the life of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0035] Figure 1 The structure diagram of the perovskite solar cell prepared in the embodiment;

[0036] Figure 2 is the structural formula of the additive in Example 1;

[0037] Figure 3 is the structural formula of the additive in Example 2;

[0038] Figure 4 is the structural formula of the additive in Example 3;

[0039] Figure 5 are the decay curves of the perovskite solar cells of the embodiments and comparative examples;

[0040] Figure 6 IV curves of the perovskite solar cells of the embodiments and comparative examples. DETAILED DESCRIPTION

[0041] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0042] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0044] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0045] Example 1

[0046] This embodiment provides a perovskite composition, which is specifically prepared by the following raw materials:

[0047] The concentration of 1.6 M (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3, 0.3 mol% of 1-octyl-3-methylimidazolium tetrafluoroborate (CAS No.: 244193-52-0), wherein 0.3 mol% refers to (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 and 1-octyl-3-methylimidazolium tetrafluoroborate have a molar ratio of 1:0.003, and the solvent in the perovskite composition is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1.

[0048] The structural formula of 1-octyl-3-methylimidazolium tetrafluoroborate is as follows Figure 2 shown.

[0049] This embodiment also provides a perovskite solar cell and a method for preparing the same, specifically:

[0050] S1: The FTO conductive glass was ultrasonically cleaned with a cleaning agent, deionized water and ethanol respectively, with each cleaning time of 20 min, and then dried with a nitrogen gun for later use;

[0051] S2: Sputtering NiO hole transport layer on dry and clean FTO conductive glass x , and then annealed on a hot plate at 200°C for 30 minutes to obtain a substrate for use;

[0052] S3: Preparation of ternary components (FA) in the glove box 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3, the concentration of the perovskite precursor solution is 1.6M, the solvent used is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1, and an ionic liquid additive is added, namely 0.3 mol% (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05)3 and 1-octyl-3-methylimidazolium tetrafluoroborate in a molar ratio of 1:0.003) of the ionic liquid additive, and stirring to obtain a perovskite precursor solution;

[0053] S4: Spin-coat the prepared perovskite precursor solution on the substrate prepared in S2, using a one-step anti-solvent extraction method, with a spin-coating speed and time of 4000 rpm and 30 s, respectively. Add 150 μL of anti-solvent chlorobenzene 10 s before the end of spin-coating, and place the spin-coated film on a baking sheet for annealing for 30 min at a temperature of 100 °C.

[0054] S5: Evaporating an electron transport layer on the prepared perovskite absorption layer, the C60 evaporation thickness is 20 nm;

[0055] S6: Place the substrate with the electron transport layer evaporated into an atomic layer deposition device and deposit the barrier layer SnO2 at 85°C for one hour;

[0056] S7: The substrate prepared in the above step is subjected to thermal evaporation coating to deposit a 100nm thick silver electrode, thereby completing the preparation of a complete perovskite solar cell, the structure of which is as follows:

[0057] FTO / NiO x / (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 / C60 / SnO2 / Ag, and the obtained perovskite solar cell is recorded as A1 cell, with the structure as Figure 1 shown.

[0058] The above ternary components (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 was prepared by weighing FAI (248.3 mg), PbBr2 (721.9 mg), CsI (20.8 mg), PbBr2 (30.1 mg), MACl (16.2 mg) and MABr (8.5 mg), and then dissolving them in DMF and DMSO (volume ratio of 4:1) to prepare a 1.6 M ternary component perovskite precursor solution (FAI). 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3.

[0059] Example 2

[0060] This embodiment provides a perovskite composition, which is specifically prepared by the following raw materials:

[0061] The concentration of 1.6 M (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3. 0.3 mol% of 1-butyl-1-methylpiperidinium tetrafluoroborate (CAS No.: 886439-34-5), the solvent in the perovskite composition is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1.

[0062] The structural formula of 1-butyl-1-methylpiperidinium tetrafluoroborate is as follows Figure 3 shown.

[0063] This embodiment also provides a perovskite solar cell and a method for preparing the same, specifically:

[0064] S1: The FTO conductive glass was ultrasonically cleaned with a cleaning agent, deionized water and ethanol respectively, with each cleaning time of 20 min, and then dried with a nitrogen gun for later use;

[0065] S2: Sputtering NiO hole transport layer on dry and clean FTO conductive glass x , and then annealed on a hot plate at 200°C for 30 minutes to obtain a substrate for use;

[0066] S3: Preparation of ternary components (FA) in the glove box 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3, the concentration of the perovskite precursor solution is 1.6M, the solvent used is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1, and an ionic liquid additive, namely 0.3 mol% of 1-butyl-1-methylpiperidinium tetrafluoroborate, is added and stirred to obtain a perovskite precursor solution;

[0067] S4: Spin-coat the prepared perovskite precursor solution on the substrate prepared in S2, using a one-step anti-solvent extraction method, with a spin-coating speed and time of 4000 rpm and 30 s, respectively. Add 150 μL of anti-solvent chlorobenzene 10 s before the end of spin-coating, and place the spin-coated film on a baking sheet for annealing for 30 min at a temperature of 100 °C.

[0068] S5: Evaporating an electron transport layer on the prepared perovskite absorption layer, the C60 evaporation thickness is 20 nm;

[0069] S6: Place the substrate with the electron transport layer evaporated into an atomic layer deposition device and deposit the barrier layer SnO2 at 85°C for one hour;

[0070] S7: The substrate in the above step is subjected to thermal evaporation coating to evaporate a 100nm thick silver electrode, thus completing the preparation of a complete perovskite solar cell, the structure of which is:

[0071] FTO / NiO x / (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 / C60 / SnO2 / Ag, and the obtained perovskite solar cell is denoted as A2 cell.

[0072] Example 3

[0073] This embodiment provides a perovskite composition, which is specifically prepared by the following raw materials:

[0074] The concentration of 1.6 M (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3. 0.3 mol% of 1-butyl-4-methylpyridinium tetrafluoroborate (CAS No.: 343952-33-0), the solvent in the perovskite composition is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1.

[0075] The structural formula of 1-butyl-4-methylpyridinium tetrafluoroborate is as follows Figure 4 shown.

[0076] This embodiment also provides a perovskite solar cell and a method for preparing the same, specifically:

[0077] S1: The FTO conductive glass was ultrasonically cleaned with a cleaning agent, deionized water and ethanol respectively, with each cleaning time of 20 min, and then dried with a nitrogen gun for later use;

[0078] S2: Sputtering NiO hole transport layer on dry and clean FTO conductive glass x , and then annealed on a hot plate at 200°C for 30 minutes to obtain a substrate for use;

[0079] S3: Preparation of ternary components (FA) in the glove box 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I0.95 Br 0.05 )3, the concentration of the perovskite precursor solution is 1.6M, the solvent used is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1, and an ionic liquid additive, namely 0.3 mol% of 1-butyl-4-methylpyridinium tetrafluoroborate, is added and stirred to obtain a perovskite precursor solution;

[0080] S4: Spin-coat the prepared perovskite precursor solution on the substrate prepared in S2, using a one-step anti-solvent extraction method, with a spin-coating speed and time of 4000 rpm and 30 s, respectively. Add 150 μL of anti-solvent chlorobenzene 10 s before the end of spin-coating, and place the spin-coated film on a baking sheet for annealing for 30 min at a temperature of 100 °C.

[0081] S5: Evaporating an electron transport layer on the prepared perovskite absorption layer, the C60 evaporation thickness is 20-25nm;

[0082] S6: Place the substrate with the electron transport layer evaporated into the atomic layer deposition equipment and deposit it at 85°C for one hour.

[0083] Deposition of barrier layer SnO2;

[0084] S7: The substrate in the above step is subjected to thermal evaporation coating to evaporate a 100nm thick silver electrode, thus completing the preparation of a complete perovskite solar cell, the structure of which is:

[0085] FTO / NiO x / (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 / C60 / SnO2 / Ag, and the obtained perovskite solar cell is recorded as A3 cell.

[0086] Example 4

[0087] This embodiment provides a perovskite composition. The difference between this embodiment and embodiment 1 is that 1-octyl-3-methylimidazolium tetrafluoroborate is 0.1 mol % and is specifically prepared by the following raw materials:

[0088] The concentration of 1.6 M (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05)3. 0.1 mol% of 1-octyl-3-methylimidazolium tetrafluoroborate. The solvent in the perovskite composition is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1.

[0089] 1 This embodiment also provides a perovskite solar cell and a method for preparing the same, specifically:

[0090] S1: The FTO conductive glass was ultrasonically cleaned with a cleaning agent, deionized water and ethanol respectively, with each cleaning time of 20 min, and then dried with a nitrogen gun for later use;

[0091] S2: Sputtering NiO hole transport layer on dry and clean FTO conductive glass x , and then annealed on a hot plate at 200°C for 30 minutes to obtain a substrate for use;

[0092] S3: Preparation of ternary components (FA) in the glove box 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3, the concentration of the perovskite precursor solution is 1.6M, the solvent used is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1, and an ionic liquid additive, namely 0.1 mol% of 1-octyl-3-methylimidazolium tetrafluoroborate, is added and stirred to obtain a perovskite precursor solution;

[0093] S4: Spin-coat the prepared perovskite precursor solution on the substrate prepared in S2, using a one-step anti-solvent extraction method, with a spin-coating speed and time of 4000 rpm and 30 s, respectively. Add 150 μL of anti-solvent chlorobenzene 10 s before the end of spin-coating, and place the spin-coated film on a baking sheet for annealing for 30 min at a temperature of 100 °C.

[0094] S5: Evaporating an electron transport layer on the prepared perovskite absorption layer, the C60 evaporation thickness is 20 nm;

[0095] S6: Place the substrate with the electron transport layer evaporated into the atomic layer deposition equipment and deposit it at 85°C for one hour.

[0096] Deposition of barrier layer SnO2;

[0097] S7: The substrate prepared in the above step is subjected to thermal evaporation coating to deposit a 100nm thick silver electrode, thereby completing the preparation of a complete perovskite solar cell, the structure of which is as follows:

[0098] FTO / NiO x / (FA 0.95 MA 0.05 )0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 / C60 / SnO2 / Ag, and the obtained perovskite solar cell is denoted as A4 cell.

[0099] Example 5

[0100] This embodiment provides a perovskite composition. The difference between this embodiment and embodiment 1 is that 1-octyl-3-methylimidazolium tetrafluoroborate is 0.5 mol % and is specifically prepared by the following raw materials:

[0101] The concentration of 1.6 M (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3. 0.5 mol% of 1-octyl-3-methylimidazolium tetrafluoroborate. The solvent in the perovskite composition is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1.

[0102] 1 This embodiment also provides a perovskite solar cell and a method for preparing the same, specifically:

[0103] S1: The FTO conductive glass was ultrasonically cleaned with a cleaning agent, deionized water and ethanol respectively, with each cleaning time of 20 min, and then dried with a nitrogen gun for later use;

[0104] S2: Sputtering NiO hole transport layer on dry and clean FTO conductive glass x , and then annealed on a hot plate at 200°C for 30 minutes to obtain a substrate for use;

[0105] S3: Preparation of ternary components (FA) in the glove box 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3, the concentration of the perovskite precursor solution is 1M, the solvent used is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1, and an ionic liquid additive, namely 0.5 mol% of 1-octyl-3-methylimidazolium tetrafluoroborate, is added and stirred to obtain a perovskite precursor solution;

[0106] S4: Spin-coat the prepared perovskite precursor solution on the substrate prepared in S2, using a one-step anti-solvent extraction method, with a spin-coating speed and time of 4000 rpm and 30 s, respectively. Add 150 μL of anti-solvent chlorobenzene 10 s before the end of spin-coating, and place the spin-coated film on a baking sheet for annealing for 30 min at a temperature of 100 °C.

[0107] S5: Evaporating an electron transport layer on the prepared perovskite absorption layer, the C60 evaporation thickness is 20 nm;

[0108] S6: Place the substrate with the electron transport layer evaporated into an atomic layer deposition device and deposit the barrier layer SnO2 at 85°C for one hour;

[0109] S7: The substrate prepared in the above step is subjected to thermal evaporation coating to deposit a 100nm thick silver electrode, thereby completing the preparation of a complete perovskite solar cell, the structure of which is as follows:

[0110] FTO / NiO x / (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 / C60 / SnO2 / Ag, and the obtained perovskite solar cell is denoted as A5 cell.

[0111] Comparative Example 1

[0112] This comparative example provides a perovskite solar cell and a preparation method thereof, specifically:

[0113] S1: The FTO conductive glass was ultrasonically cleaned with a cleaning agent, deionized water and ethanol respectively, with each cleaning time of 20 min, and then dried with a nitrogen gun for later use;

[0114] S2: Sputtering NiO hole transport layer on dry and clean FTO conductive glass x , and then annealed on a hot plate at 200°C for 30 minutes to obtain a substrate for use;

[0115] S3: Preparation of ternary components (FA) in the glove box 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3, the concentration of the perovskite precursor solution is 1.6M, the solvent used is DMF (dimethylformamide): DMSO (dimethyl sulfoxide) = 4:1, and the perovskite precursor solution is obtained by stirring evenly;

[0116] S4: Spin-coat the prepared perovskite precursor solution on the substrate prepared in S2, using a one-step anti-solvent extraction method, with a spin-coating speed and time of 4000 rpm and 30 s, respectively. Add 150 μL of anti-solvent chlorobenzene 10 s before the end of spin-coating, and place the spin-coated film on a baking sheet for annealing for 30 min at a temperature of 100 °C.

[0117] S5: Evaporating an electron transport layer on the prepared perovskite absorption layer, the C60 evaporation thickness is 20-25nm;

[0118] S6: Place the substrate with the electron transport layer evaporated into an atomic layer deposition device and deposit the barrier layer SnO2 at 85°C for one hour;

[0119] S7: The substrate in the above step is subjected to thermal evaporation coating to evaporate a 100nm thick silver electrode, thus completing the preparation of a complete perovskite solar cell, the structure of which is:

[0120] FTO / NiO x / (FA 0.95 MA 0.05 ) 0.95 Cs 0.15 Pb(I 0.95 Br 0.05 )3 / C60 / SnO2 / Ag, and the obtained perovskite solar cell is denoted as B cell.

[0121] Comparative Example 2

[0122] This comparative example provides a perovskite solar cell and a preparation method thereof. The difference between this comparative example and Example 1 is that guanidine tetrafluoroborate (GuaBF4) is used as an additive composed of guanidine cations and tetrafluoroborate anions, and the additive with CAS number 36595-00-3 replaces the 1-octyl-3-methylimidazole tetrafluoroborate in Example 1. The other conditions are the same and are recorded as C batteries.

[0123] Test Case

[0124] This test example uses a simulated light source system to test the photovoltaic performance of the obtained perovskite solar cells: A1 cell, A2 cell, A3 cell, and B cell. The photovoltaic performance test results are shown in Table 1:

[0125] Table 1. Photovoltaic performance test

[0126]

[0127]

[0128] The guanidine salt in the present invention has a large ionic radius and can be inserted into the perovskite lattice. In some cases, it can distort the structure of the perovskite, improve the crystal structure of the perovskite, and adjust its band gap, thereby improving the photoelectric performance of the perovskite. In the present invention, the nitrogen atom of the imidazole in Example 1 can provide a lone pair of electrons that can bind to the uncoordinated Pb in the perovskite. 2+ and I - The formation of complex can passivate defects in the perovskite film; the pyridine ring in Example 3 is an electron-rich chemical structure, which can provide electrons to neutralize trap states; the piperidine additive in Example 2 improves the open circuit voltage and battery efficiency, and also delays the component separation of the impurity phase and the formation of pinholes in the perovskite absorption layer; the three additives of the present invention are accumulated at the grain boundaries, which can regulate the growth of perovskite crystals and further improve the quality of the film, thereby passivating defects, and can also protect the grain boundaries from ion migration induced by water vapor or heating, further enhancing the environmental stability of the battery.

[0129] Figure 5 This is the cell attenuation curve of a perovskite solar cell placed at 70% RH and 25°C. The horizontal axis is the placement time, and the vertical axis is the normalized efficiency. At 70% RH and 25°C, the perovskite solar cell is placed for x days, and the cell efficiency decays to y% of the initial efficiency. The closer the attenuation data is to 1, the better the stability. Figure 5 At 70% RH and 25°C, the B battery only maintained 31.7% of the initial efficiency after 30 days of storage. In contrast, the stability of the A1 / A2 / A3 batteries with the three additives of the present invention was significantly improved, especially the A1 battery, which only maintained 96.6% of the initial efficiency after 30 days of storage, and the efficiency did not drop significantly. This shows that the three additives of the present invention have excellent stability.

[0130] From Table 1 and Figure 6 It can be seen that the heterocyclic structure having N atoms and containing BF provided by the present invention 4- After the anionic ionic liquid was used as an additive to passivate the perovskite absorber layer, the short-circuit current (J sc ) and fill factor (FF) have been significantly improved, thereby greatly improving the photoelectric conversion efficiency of perovskite solar cells. In particular, the A1 cell prepared using 1-octyl-3-methylimidazolium tetrafluoroborate has a photoelectric conversion efficiency that is nearly 2% higher than that of the B cell. This is mainly due to the use of the N-atom heterocyclic structure provided by the present invention and containing BF 4- The result is the passivation of anions by ionic liquids.

[0131] The above content describes the embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A perovskite composition, characterized in that: The raw materials for preparing the perovskite composition include: (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and additives; The additive comprises at least one of 1-octyl-3-methylimidazolium tetrafluoroborate, 1-butyl-1-methylpiperidinium tetrafluoroborate and 1-butyl-4-methylpyridinium tetrafluoroborate.

2. The perovskite composition according to claim 1, characterized in that Said (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 and the additive in a molar ratio of 1:0.001 to 0.

005.

3. The perovskite composition according to claim 1, characterized in that In solution, the (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 concentration is 1~1.8mol / L.

4. The perovskite composition according to claim 1, characterized in that In a solution state, the solvent of the perovskite composition includes at least one of dimethylformamide and dimethyl sulfoxide.

5. The perovskite composition according to claim 4, characterized in that In a solution state, the solvent of the perovskite composition includes dimethylformamide and dimethyl sulfoxide; the molar ratio of the dimethylformamide to the dimethyl sulfoxide is 4:

1.

6. A perovskite film, characterized in that: The perovskite film is prepared from the perovskite composition according to any one of claims 1 to 5.

7. A perovskite solar cell, characterized in that: It comprises an anode conductive glass layer, a hole transport layer, a perovskite absorption layer, an electron transport layer, a blocking layer and a cathode layer which are stacked in sequence, and the perovskite absorption layer is the perovskite film according to claim 6.

8. The perovskite solar cell according to claim 7, characterized in that: The preparation method of the perovskite absorption layer comprises: coating the titanium ore composition on the hole transport layer in a solution state, adding an anti-solvent for extraction during spin coating, and then performing annealing to obtain the perovskite absorption layer.

9. The perovskite solar cell according to claim 8, characterized in that: The annealing temperature is 100-120°C.

10. The perovskite solar cell according to claim 7, characterized in that: The material of the electron transport layer includes C60.

Citation Information

Cited By

  • Perovskite precursor solution, perovskite solar cell and preparation method thereof

    CN119855468A